2020
DOI: 10.1111/ijac.13660
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties and flexural strength of a monolithic zirconia submitted to grinding and regenerative heat treatment

Abstract: The present study evaluated the average (Ra) and total (Rz) roughness, crystallography (XRD), flexural strength (FS), and Weibull modulus (m) of a monolithic zirconia subjected to grinding (G) and heat treatments (HT). Specimens were submitted or not to grinding with a diamond stone in low rotation. HT was conduced in two protocols, one at 900°C for 60 minutes and the other at 1000°C for 30 minutes. Roughness was evaluated in a profilometer, crystallography in X‐ray diffractometer, and FS by four‐point flexura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Zirconium oxide [ 9 , 10 , 11 , 12 , 13 ] is the most investigated ceramic dental material, with much of the work being performed in the laboratory rather than in clinical applications. This is because of its intrinsic weaknesses such as brittleness and poor impact resistance, which mainly results from its low-temperature degradation upon aging [ 14 , 15 , 16 ]. To address these problems, some researchers have mixed iridium oxide with zirconium oxide, but these composites exhibited unsuitable in vivo properties [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zirconium oxide [ 9 , 10 , 11 , 12 , 13 ] is the most investigated ceramic dental material, with much of the work being performed in the laboratory rather than in clinical applications. This is because of its intrinsic weaknesses such as brittleness and poor impact resistance, which mainly results from its low-temperature degradation upon aging [ 14 , 15 , 16 ]. To address these problems, some researchers have mixed iridium oxide with zirconium oxide, but these composites exhibited unsuitable in vivo properties [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…R a and R z are important parameters reflecting the effect of surface treatment. [30,31] It should be noticed that it is greatly affected by scratches, pollution, and measurement noise due to its peak correlation. The R a and R z for sandblasting surface were the largest, but they had the most minor interlayer adhesion strength with the substrate.…”
Section: The Effect Of the Surface State Of Nab Substrate On Coating ...mentioning
confidence: 99%
“…It also suggested that sandblasted zirconia implants can achieve higher stability in bone than machined zirconia implants and positively affect the interfacial shear strength (28). However, the mechanical forces formed during sandblasting will induce LTD (29). Even though LTD simulated by steam autoclave aging has few significant effects on the roughness, it still needs highlighting that the specimen preparation processing has a high impact on forming LTD (30).…”
Section: Physical Treatment Sandblastingmentioning
confidence: 99%